Influence of electrolyte proportion on the performance of dye-sensitized solar cells - Peng Gu; Dingyu Yang; Xinghua Zhu; Hui Sun; Peihua Wangyang; Jitao Li; Haibo Tian (AIP Advances, 2017)
The performance of dye-sensitized solar cells (DSSC) depends strongly on the electrolyte. In this paper, the electrolytes with various solvents and different potassium iodide (KI) & iodine (I2) concentration were prepared and their influence on the DSSC performance were investigated. The results revealed DSSC with electrolyte prepared by organic solvent show better performance than that of inorganic solvent. Meanwhile, the increasing of KI concentration from 0.1 to 0.6 mol/L can effectively improve the short-circuit current density (Jsc) from 0 2, correspondingly, the DSSC conversion efficiency (η) increased from 0.04% to 0.11%. On the other hand, the Jsc and η of DSSC increased firstly then decreased with the I2 concentration raised from 0.025 mol/L to 0.125 mol/L. It is worth to notice that the open-circuit voltage (Voc) of DSSC is almost unchanged with the concentration of KI and I2. In this paper, the best performance DSSC (Jsc=0.87 mA/cm2, Voc=0.57 mV, η=0.23%) can be obtained with electrolyte at a KI and I2 concentration of 0.6 mol/L and 0.075 mol/L respectively. Finally, the electrolytes used water and mixture of acetonitrile & ethylene glycol as solvents showed the latter presented better stability after setting at room temperature for 72 hours.